Market valuation of employee stock options - Aboody, David (Journal of Accounting and Economics, 1996)
This study investigates whether investors incorporate the value of a firm's outstanding employee stock options into its stock price. I estimate the outstanding options' value for a sample of firms for which outstanding fixed options exceed 5% of outstanding common shares in 1988. I find a negative correlation between the value of outstanding options and a firm's share price. The correlation is stronger (i) for the option's intrinsic value than for the option's time value, (ii) for options that are later in their vesting stage than earlier in their vesting stage, and (iii) for large firms than for small firms. In addition, the FASB's method for calculating compensation expense has no explanatory power in the presence of this paper's calculation of the options' value.